High-intensity focused ultrasound (HIFU) hemiablation of the prostate: late follow-up MRI findings in non-recurrent patients - Schaudinn, Alexander; Michaelis, Jakob; Franz, Toni; Ho-Thi, Phuc; Horn, Lars-Christian; Blana, Andreas; Hadaschik, Boris; Stumpp, Patrick; Stolzenburg, Jens-Uwe; Schlemmer, Heinz-Peter; Denecke, Timm; Busse, Harald; et al. (European journal of radiology, 2021)
Objectives - Focal therapy with high-intensity focused ultrasound (HIFU) is an emerging option for the treatment of prostate cancer and often followed up by MRI. Image assessment of treatment failure, however, requires proper knowledge about typical procedure-related changes in prostate MRI, which is sparse, in particular for unilateral HIFU treatment and late follow up (beyond 6 months). The goal of this study was therefore to compile the type and frequency of such MRI findings in selected patients without recurrent cancer 12 months after prostate hemiablation. - Methods - Data from a prospective multicenter trial on HIFU hemiablation were reviewed retrospectively. Trial patients have had a late follow-up by MRI (at around 12 months) and either MRI/transrectal ultrasound (TRUS) fusion or standard TRUS-guided biopsy. This work deliberately included patients with non-recurrent cancer in the treated prostate lobe in per-protocol biopsy leaving 30 men with initial International Society of Urological Pathology (ISUP) Grade Group of 1 or 2. Six categories of potential HIFU-related MRI features were assessed by an expert committee and then evaluated by two readers in consensus: 1. shrinkage of the treated lobe, 2. residual prostate tissue, 3. fluid-filled cavity, 4. fibrosis, 5. hematoma residuals (in the prostate or seminal vesicles) and 6. contrast enhancement of the ablated area. - Results - Shrinkage of the ablated lobe was seen in 93% of the cases with an average percent volume change of −37% (range: −70% to +108%). In the contralateral lobe, the volume remained practically the same (-2% on average, p = 0.804). In the ablated lobe, the frequency of fibrosis was 97%. Residual prostate tissue was seen in 93% of the cases. The frequency for fluid-filled cavities was 97%, with the wide majority (90%) contiguous with the urethra. Hematoma residuals in the prostate and in seminal vesicles were found in 47% and 10% of the patients, respectively. Contrast enhancement was both rim-like (50%) as well as diffuse (33%) within the ablated area. - Conclusion - In our case series of HIFU hemiablation in the prostate, shrinkage, residual prostate tissue, fluid-filled cavities contiguous with the urethra and fibrosis were very common late MRI findings of the ablated lobe in non-recurrent patients. Rim-like contrast enhancement or diffuse one within the ablated area were less frequent.
Gesehen am 08.02.2022